Effect of exhaust gas recirculation and compression ratio on combustion characteristics and NOx emissions in an NH3/H2O2 fueled HCCI engine - Kabbir Ali; Abubaker A.M. Mohammedali; Mohamed I Hassan Ali (Energy Conversion and Management: X)
This study investigates the impact of exhaust gas recirculation (EGR) and compression ratio (CR) on the combustion characteristics and NOx emissions of an NH3/H2O2-fueled homogeneous charge compression ignition (HCCI) engine. Utilizing both 3D Computational Fluid Dynamics (CFD) and 1D-Chemkin-Pro models, the research explores the effects of varying NH3 and H2O2 mixtures to optimize engine performance and emissions. The study reveals that increasing EGR from 0 % to 40 % resulted in a reduction of in-cylinder pressure and HRR, particularly at a 20 % H2O2 volume fraction. At higher H2O2 concentrations (30 % and 40 %), the diluting effects of EGR were less pronounced. NOx emissions decreased significantly with increased EGR, with a reduction in peak combustion temperatures by approximately 25–65 K, leading to a decrease in NOx emissions by about 3 %. Reducing the CR from 17.1 to 14.2 led to a decrease in in-cylinder pressure and temperature, which in turn reduced the maximum pressure rise rate and NOx emissions. NOx emissions decreased by approximately 50 %, 12 %, and 8 % when the CR was reduced from 17.1 to 14.2 at H2O2 contents of 20 %, 30 %, and 40 %, respectively. Output power increased from 2.63 kW to 10.6 kW at an H2O2 volume fraction of 20 %, while at a higher H2O2 concentration of 40 %, it rose from 12.4 kW to 13.9 kW. Brake thermal efficiency and indicated thermal efficiency decreased with increasing EGR, but higher H2O2 concentrations helped sustain efficiency levels close to 50 % even under high EGR conditions. The findings highlight the potential of NH3/H2O2 as an alternative fuel, with EGR and CR adjustments offering substantial benefits in reducing emissions and enhancing engine adaptability. This research supports the development of sustainable combustion technologies that comply with stringent environmental standards.